2016
DOI: 10.1136/injuryprev-2015-041932
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of regional migration and the risks of attempted suicide and violent assault injury

Abstract: ObjectivesWe study the association between changing residence and risks of attempted suicide and violent assault injury in Alberta, Canada. Our primary objective is to understand whether a change in residence between urban, rural and semiurban areas is associated with increased risk of intentional injury. Methods Study subjects are a cohort of residents linked to data on emergency department and inpatient hospital admissions between 1999 and 2010. We used generalised estimating equations to model the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The provincial government charges a healthcare insurance premium to Albertans and provides reductions of the premium for low income families. In this study, families without financial assistance for insurance premium were classified into high SES and families receiving assistance for their premiums (ie, full premium subsidy groups, partial premium subsidy groups, welfare groups with premiums waived, and FN treaty‐status Aboriginals) were categorized into low SES as done in previous studies . Healthcare premiums for all First Nations who have Treaty status are paid by the Federal government.…”
Section: Methodsmentioning
confidence: 99%
“…The provincial government charges a healthcare insurance premium to Albertans and provides reductions of the premium for low income families. In this study, families without financial assistance for insurance premium were classified into high SES and families receiving assistance for their premiums (ie, full premium subsidy groups, partial premium subsidy groups, welfare groups with premiums waived, and FN treaty‐status Aboriginals) were categorized into low SES as done in previous studies . Healthcare premiums for all First Nations who have Treaty status are paid by the Federal government.…”
Section: Methodsmentioning
confidence: 99%
“…However, at least some groups of migrants may be affected by elevated health (including mental health) risks. For example, it has been shown that internal migration within Canada is associated with an increased risk of suicide attempts (Yiannakoulias, Sanchez‐Ramirez, Svenson, & Voaklander, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Racial differences in SES are also closely associated with racial disparities in health and psychosocial well-being among AA and Hispanics [14, 19]. This may directly contribute to the higher prevalence of HS in patients with SOC.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…HS is reportedly more common in individuals of low SES [8], which is more prevalent in African and Hispanic populations, especially in the USA [14, 19]. Racial differences in SES are also closely associated with racial disparities in health and psychosocial well-being among AA and Hispanics [14, 19].…”
Section: Socioeconomic Statusmentioning
confidence: 99%
See 1 more Smart Citation